ETHICS AND LANGUAGE: AN ANALYTICAL REVIEW OF LINGUISTIC INFLUENCE ON ETHICAL DECISION-MAKING - Ahsan Mukhtar; Shazia Aslam; Tanveer Fatima (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper examines one of the most crucial areas of concern – language and ethics – through a critical analysis of how the choices made of language impact on the ethical concerns prevalent in different areas of practice. The paper reviews the effects of moral aspects of language framing in what concerns the problem of the so-called ‘framing effect,’ which refers to the differences in terms of ethical choices given the specifics of the linguistic representations used in framing a particular problem. Furthermore, the review also discusses the question of ethical uses of language in political, legal and media contexts as language can either be used to foster or negate ethical values. For example, employment of white-washing in political language can mask the ethical implications of policies as well as in bias language legal repercussions. Speculative in orientation, the study also discusses the content which promotes the rhetoric of ethical norms; the role of storytelling and metaphor in ethical thinking. The paper concludes with an evaluation of recommendation for increasing ethical language use in professional and public discourse with a view of increasing accountability and morality in communication practices.